The responses of lager brewing yeast to low temperatures - Somani, Abhishek (2013)
The removal of yeast biomass (cropping) at the end of fermentation to inoculate a subsequent fermentation (serial-repitching) is common practice in the brewing industry. Between successive fermentations cropped yeast is stored as a slurry in cooled storage vessels under anaerobic conditions until required for subsequent use. Maintenance of yeast quality during storage is critical for subsequent fermentation performance. An assumption is made in brewing that all strains benefit from storage at 3-4°C. To test this assumption a model working system was initially established to assess cooling times of lager yeast in different suspension media. Preliminary investigations focussing on freshly propagated yeast slurry demonstrated that whilst the deleterious effects of extremely high storage temperatures on lager brewing yeast physiology was in line with expectation, utilization of traditionally recommended storage temperatures does not necessarily benefit yeast physiology when compared to slurry maintenance at slightly higher temperatures. Genome-scale transcriptional analysis in slurries cropped following an initial fermentation suggested that lager yeast might experience cold stress during slurry maintenance at typically recommended storage temperatures. In contrast, maintenance of lager yeast at a slightly higher storage temperature, in this case 10°C, yielded no adverse impact on key indicators of brewing yeast physiological state or on subsequent fermentation profiles following repitching into fermentations. Whilst these observations were not made using full production scale, they do indicate that optimal storage may not be currently being deployed for brewing yeast at full scale.